2003
DOI: 10.1242/jeb.00622
|View full text |Cite
|
Sign up to set email alerts
|

Photobehavior of stony corals: responses to light spectra and intensity

Abstract: SUMMARY Tentacle expansion and contraction were investigated in four zooxanthellate coral species and one azooxanthellate coral (Cladopsammia gracilis). Favia favus, Plerogyra sinuosa and Cladopsammia gracilisexpand their tentacles at night, while tentacles in Goniopora lobataand Stylophora pistillata are expanded continuously. Light at wavelengths in the range 400-520 nm was most effective in eliciting full tentacle contraction in F. favus and in P. sinuosa. Higher light intensities in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 29 publications
3
114
0
Order By: Relevance
“…As other existing holobiont photoprotective mechanisms, such as MAA accumulation, act outside the yellow-orange range, the CPs in shallow-water corals might provide protection in a vulnerable spectral window, functioning in a similar manner as anthocyanins in higher plants (Merzlyak et al 2008). Finally, important physiological processes in corals, including regulation of genes encoding GFP-like proteins, are controlled by blue light (Levy 2003;Levy et al 2006;Kaniewska et al 2009). Hence, the removal of photons in the longer wavelength range appears to be a sensible strategy to avoid interference between photoprotection and blue-light-regulated processes.…”
Section: Discussionmentioning
confidence: 99%
“…As other existing holobiont photoprotective mechanisms, such as MAA accumulation, act outside the yellow-orange range, the CPs in shallow-water corals might provide protection in a vulnerable spectral window, functioning in a similar manner as anthocyanins in higher plants (Merzlyak et al 2008). Finally, important physiological processes in corals, including regulation of genes encoding GFP-like proteins, are controlled by blue light (Levy 2003;Levy et al 2006;Kaniewska et al 2009). Hence, the removal of photons in the longer wavelength range appears to be a sensible strategy to avoid interference between photoprotection and blue-light-regulated processes.…”
Section: Discussionmentioning
confidence: 99%
“…In many faviid corals, for instance, high irradiance leads to tissue contraction, while dim light or darkness leads to tissue expansion (Levy et al, 2003). It has been suggested that tissue contraction has a photoprotective role, while tissue expansion enhances photosynthesis (Fabricius and Klumpp, 1995;Brown et al, 2002).…”
Section: Research Articlementioning
confidence: 99%
“…It is not likely that the expansion state of the polyps played a role in this response, as Levy et al (Levy et al, 2003) found no differences in the maximum quantum yield of expanded versus contracted tentacles in different coral species. Given the intermittent nature of the stress, the lower cumulative photoinhibition in corals subjected to low temperature might be related to an enhanced photoprotection (Krämer et al, 2012) and/or repair (Hill et al, 2011) at lower temperature.…”
Section: Discussionmentioning
confidence: 97%
“…However, the retraction/expansion of polyps during the day is supposed to enhance the planar density and photosynthetic performance of Symbiodinium, as more endosymbionts will be exposed to the light (Sebens and DeRiemer, 1977;Lasker, 1979). However, polyp expansion and retraction also respond to a variety of other factors irrespective of the light:dark cycle, such as differences in light intensities (Gladfelter, 1975;Levy et al, 2003), current speed (Sebens et al, 1997), food availability (Levy et al, 2001), polyp size (Lasker, 1981), interactions between the aforementioned factors, and the physiological needs of the coral colony (Porter, 1976).…”
Section: Introductionmentioning
confidence: 99%